ANALISIS PERHITUNGAN PAJAK PENGHASILAN KARYAWAN PADA PT.KDC SAMARINDA - Mardiana, Mardiana; Rismawati, Fibby (LPPM University 17 Agustus 1945 Samarinda, 2019)
The purpose of this study is to determine the calculation of income tax (PPh) Article 21 for employees of PT.KDC Samarinda is in accordance with Law Number 36 of 2008 and Minister of Finance Regulation Number 101 / PMK.010 / 2016. Tax is a compulsory contribution to the State owed by an individual or entity that is a force based on the Law, by not getting compensation directly and used for the State's needs for the greatest prosperity of the people. Income is any additional economic capability that is received or obtained by taxpayers, both from Indonesia and from outside Indonesia, which can be used for consumption or to increase the wealth of the taxpayer concerned, by name and in any form.Article 21 Income Tax is a tax on income in the form of salary, wages, honorarium, allowances, and other payments in whatever name and form in connection with employment or position, services, and activities carried out by individuals of domestic tax subjects, as referred to in Article 21 Income Tax Law.The analytical tool used in this study is the amount of individual taxpayer tariffs Article 17 of Law Number 36 of 2008. Changes in the amount of Non-Taxable Income (PTKP) according to Minister of Finance Regulation 101 / PMK.010 / 2016 and office fees according to UU- Law Number 36 of 2008 article 21 paragraph 3The results of this study of Income Tax Calculation (PPh) of employees with permanent employee status at PT. KDC Samarinda are in accordance with Law Number 36 of 2008 and Regulation of the Minister of Finance Number 101 / PMK.010 / 2016